Hit by the wave: a case of painful Horner's and intramural haematoma of the carotid. (12th September 2018) - Umana, Etimbuk; Bajwa, Raazi; Davidson, Ian; Gallagher, David
Abstract : Carotid artery dissection from rupture of the vasa vasorum is under-recognised. We report the case of a 60-year-old woman presenting to our hospital with a 2-week history of right-sided headache, neck pain, unequal pupils and ptosis after being hit by a wave on the beach. She was diagnosed with painful Horner's syndrome. MR angiogram revealed dissection of the right internal carotid artery with an intramural haematoma without an intimal flap. A diagnosis of carotid artery dissection from rupture of the vasa vasorum was made. Initial antithrombotic (aspirin and clexane) were stopped as she was deemed a low stroke risk with no signs of ischaemia on MR brain. Her clinical course was uneventful with resolution of the intramural haematoma seen on repeat MR angiogram.